1999
DOI: 10.1038/sj.bjc.6690220
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia significantly reduces aminolaevulinic acid-induced protoporphyrin IX synthesis in EMT6 cells

Abstract: SummaryWe have studied the effects of hypoxia on aminolaevulinic acid (ALA)-induced protoporphyrin IX (PpIX) synthesis in EMT6 monolayer cultures characterized by different cell densities and proliferation rates. Specifically, after ALA incubation under hypoxic or normoxic conditions, we detected spectrofluorometrically the PpIX content of the following populations: (a) low-density exponentially growing cells; (b) high-density fed-plateau cells; and (c) high-density unfed-plateau cells. These populations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…However, cells treated under these conditions were often compared to cells cultured under air, incorrectly inferring that this oxygenation was representative of "healthy" tissues, and studies have often used short-term decreases in O 2 concentration [4,5], rather than longer periods associated with disease. Additionally, air has been used to represent post-reperfusion oxygenation when modelling reperfusion events in vitro [55,56].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, cells treated under these conditions were often compared to cells cultured under air, incorrectly inferring that this oxygenation was representative of "healthy" tissues, and studies have often used short-term decreases in O 2 concentration [4,5], rather than longer periods associated with disease. Additionally, air has been used to represent post-reperfusion oxygenation when modelling reperfusion events in vitro [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Non-melanoma skin cancers are the most common form of cancers diagnosed annually in the western world and, despite low mortality, the associated high morbidity [15] provides a significant incentive to identify improved, cosmetically acceptable treatments. Previous studies have considered the effects of hypoxia on the outcome of photodynamic therapies [5,16], although these were limited in their scope and did not attempt to recapitulate the O 2 https://doi.org/10.1016/j.freeradbiomed.2018.08.025 Received 22 July 2018; Accepted 20 August 2018 environment in which superficial epidermoid carcinomas reside. The use of a physiologically accurate in vitro model would therefore support the successful translation of experimental findings into in vivo investigations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxygen tension and pH of the cellular environment were shown to affect the production of PpIX in exponentially growing bladder cancer cells (Wyld et al, 1998). Georgakoudi et al (1999) reported the effect of the combination of hypoxia, cell density and proliferation rate on PpIX production in EMT6 cells in monolayer cell culture. They demonstrated that PpIX is synthesized less effectively under hypoxia than in normoxic conditions, with the magnitude of the effect of hypoxia being strongly dependent on cell density and proliferation status.…”
mentioning
confidence: 99%